PENGEMBANGAN KOMODITAS POTENSIAL DAN PERANANYA TERHADAP PERLUASAN KESEMPATAN KERJA DAN PENANGGULANGAN KEMISKINAN DI KABUPATEN SELUMA - Trisna Yanti, Rina (JURNAL EKOMBIS REVIEW, 2015)
Rina Trisna Yanti; The purpose of this study was to determine the role of potential commodities for Employment Expansion in Seluma and To determine the role of potential commodities against Poverty Seluma. This type of research is the study deskriptifkualitatif. This study did not test the hypothesis but only describe the information is in accordance with the study. The results showed that the oil palm which is a potential commodity in Seluma absorb manpower with the data the period 2006-2011 in general has increased it is also supported by an explanation of the Department / Institution related and members of farmer groups in Seluma. With palm oil commodity Seluma poverty decreased among those who work on oil palm, it is known from Department / Institution related to channel social assistance to the poor in Seluma decline in population work as farmers palm oil.Keywords: Potential Commodities, Employment, Poverty Reduction